Applications of 3D printing in medicine: A review - Chensong Dong; Marko Petrovic; Ian J. Davies (Annals of 3D Printed Medicine, 2024)
3D printing, or additive manufacturing, has transformed various industries with its layer-by-layer fabrication approach. In medicine, 3D printing, or biofabrication, has seen significant advancements, particularly in the creation of patient-specific medical models and custom-made drug tablets. Bioprinting, a key aspect of biofabrication, encompasses three approaches: biomimicry, autonomous self-assembly, and microtissues, each with its unique advantages and disadvantages. This comprehensive review explores the merits and limitations of these bioprinting approaches and outlines the three main phases of the entire bioprinting process: pre-processing, processing, and post-processing. By enhancing patients’ quality of life, reducing healthcare costs, and tapping into the global medical device market, biofabrication technologies hold immense promise for the future of medicine. This literature review focuses on the applications of 3D printing technologies in creating medical devices, including bone tissues, joint tissues, 3D printed tablets, and medical models.